EASYMATH2U: learning mathematics beyond the classroom - Ngarisan, Noor Syazana; Mahadi, Shafaruniza; Md Nasrudin, Farah Suraya; Harun, Nurul 'Aini; Lehat, Mohd Lezam (Universiti Teknologi MARA, Johor, 2025)
Gaining proficiency in the mathematics subject necessitates ongoing practice and is aimed at achieving a more profound comprehension of a concept or method. This implies that learners must consistently revisit their studies to enhance their mathematical abilities. Nevertheless, the majority of students struggle to achieve this, as they typically rely on their teachers, peers, and family members for inspiration, feedback, or clarification on answers. In addition, students frequently depend on various learning resources such as notes, textbooks, and tutorials, which can be daunting and complicate their ability to absorb and understand all the knowledge. In line with the passage of time and the current generation, teachers need to think of more flexible and appealing techniques or methods to attract students to try more questions and not just rely on pen and paper.